Indonesia's National Defense Strategy in Facing the Threat of Changes in the Strategic Environment - Wahid, Muhamad Hasanuddin; Banyu Perwita, Anak Agung; Thamrin, Suyono; Widjayanto, Joni (Faculty of Law, Universitas Pekalongan, 2024)
Received: 2023-11-16Revised: 2024-02-12Accepted: 2024-03-19 Keywords:Global and Regional Environmental Strategy; Security Vulnerabilities and Threats; International Cooperation;Arms Race;Sustainable Development and National SecurityThe aim of this research is how Indonesia responds to changes in environmental strategy, in building protection capabilities for the implementation of national development. For this reason, it is necessary to identify weaknesses and vulnerabilities that can be exploited by the state or the external sector to achieve goals. The research method used is a qualitative method, while for threat analysis used is the Means, Ways, and method, namely, how to understand, disseminate and formulate existing threat strategies. This method consists of three parts that are interconnected with each other. The research results show. Global and regional environmental developments are marked by the emergence of several new problems that will have a significant impact on human development in the future. During long- standing problems and conflicts, international cooperation is the only option that offers hope for international peace and stability. The role of large countries and their dominant influence remains the main feature of global and regional environmental strategy. Opportunities for developing countries to increase their economic competitiveness and bargaining power are limited due to the increasing economic, political, defense and security power of several countries in various regions. In this context, new breakthroughs in prioritizing the environment, increasing national damage, and implementing sustainable development are urgently needed. The proliferation of nuclear weapons and nuclear nuclear development programs by several countries, such as North Korea and Iran, poses a threat to global security and the potential use of nuclear weapons in a war between Russia and Ukraine. Strengthening global and regional political and security policies in the future when many countries will emerge with economic and military strength. The arms race is intensifying, of strategic importance to countries around the world. Indonesia needs to have close relations with several countries such as Australia, Russia, China, and the United States. Efforts to build mutually beneficial relationships need to be prioritized to realize Indonesia's strategic interests in the medium and long term. On the other hand, Indonesia has and will face several vulnerabilities and even threats. Problems related to energy supply, population, environment, economy, separatism, and many transnational security issues need to be addressed immediately with sustainable action. To overcome these problems, it is necessary to adjust strategies, improve the ideological, political, economic, socio-cultural and security conditions for preserving Indonesia, as well as maintaining the integrity of the state and the sovereignty of the Republic of Indonesia. continue to increase national capacity. Security of Indonesian citizens.